Recurrent abdominal and lower limb venous thrombosis due to inherent protein-C and protein-S deficiency - Polavarapu, Naren; Narayanasamy, Senthil; Subramanian, Naveen Arunachalam (International Journal of Research in Medical Sciences, 2019)
Protein-C and protein-S deficiency is associated with a hypercoagulable state which usually presents with recurrent venous thrombosis as a common complication. But extensive thrombosis involving all the major abdominal and lower limb veins is quite rare. Here, we report a case of a 27-year-old woman presented with engorged veins all over abdomen and chest since 20 days. Clinical examination revealed signs suggestive of portal venous hypertension with moderate splenomegaly. Protein-C and protein-S levels were found to be low. Portal venous doppler ultrasound and CT-venogram revealed chronic thrombosis of portal vein, inferior vena cava, bilateral iliac and femoral veins with extensive collaterals formation and partial thrombosis in collaterals as well. The patient was successfully managed with anti-coagulating agent (acenocoumarol) and has been maintained on regular follow-up to avoid reoccurrence of thrombosis.